Pengaruh Online Customer Trust Dan Online Store Environment Terhadap Online Impulse Buying Melalui Perceived Enjoyment Sebagai Variabel Mediasi (Studi pada Konsumen TikTok Shop) - Sherly Regita Cahyani; Yessy Artanti (Jurnal Ilmu Manajemen, 2023)
The ease of accessing social commerce causes online impulse buying to increase significantly. Knowing and discussing the relationship between online customer trust, online store environment, perceived enjoyment, and online impulse buying is the main objective of this study. The independent variables used in this study are online customer trust and online store environment to find out why someone experiences online impulse buying, using a mediating variable by perceived enjoyment with the aim of whether these mediation variables can strengthen the relationship between online customer trust and online store environment variables with online impulse buying. This study used a purposive sampling method, using 110 respondents obtained by online questionnaires. Using the SEM model with AMOS software. This study's results indicate an influence between online customer trust, online store environment, perceived enjoyment, and online impulse buying. This research is helpful for future research as well as social commerce, especially the TikTok Shop, to pay more attention and care about the importance of online customer trust, the online shop environment, and perceived enjoyment by consumers. This research has implications that the social commerce company TikTok Shop has a vital role in maintaining customer trust and enjoyment in shopping online, so consumers do not hesitate to make purchases.